Denudação química e implicações na composição das águas superficiais da Bacia do Rio Jaú (SP) - Sardinha, Diego de Souza [UNESP]; Bonotto, Daniel Marcos [UNESP]; Godoy, Letícia Hirata [UNESP]; Conceição, Fabiano Tomazini da [UNESP]; Moreno, Maria Margarita Torres [UNESP] (Revista Brasileira de Geomorfologia, 2012)
This work evaluated the geochemical denudation and implications in the composition of surface waters from Jaú River basin, six sampling points were established and six fi eld campaigns were carried out in 08/14/2009, 09/17/2009, 10/17/2009, 11/20/2009, 12/23/2009 and 01/12/2010, which involved the dry and wet periods. The analyses were executed for discharge, temperature, pH, electric conductivity, calcium, magnesium, sodium, potassium, silicon dioxide, alkalinity, chloride, sulfate, phosphate and nitrate. The results indicated that calcium, magnesium and nitrate have similar behavior, i.e. the amount increases upstream (P1 and P3, sediments of Itaqueri Formation and the Middle Hills relief unit) to downstream (P2 and P4, Hillock Elongated and Spikes associated with igneous rocks of the Serra Geral Formation). P5 and P6 also drain the basalts of Serra Geral Formation in Jaú River, where except for Ca2+, Mg2+ and Cl- all other parameters have a higher concentration at the point P6, near the Tietê River mouth. However, the total cations and anions (t/km2 /year) is greater in point P5, due to the higher concentration of Ca2+ and Mg2+. Because the rocks at Jaú River don´t have Cl- , NO3 - , PO4 3- and SO4 2- bearing minerals as a main constituent, the chemical denudation (t/year) in Jaú River basin was calculated based on the concentration of Ca2+, Mg2+, Na+ , K+ and SiO2 (leached solution of minerals that make up the basin rocks). The results indicated that the Jaú River basin exports about 16,000 tons of weathered material per year to Tietê River.

Este trabalho avaliou a denudação química e suas implicações na composição das águas superfi ciais da bacia do Rio Jaú, seis pontos de amostragem foram estabelecidos e realizaram-se seis amostragens (14/08/2009, 17/09/2009, 17/10/2009, 20/11/2009, 23/12/2009 e 12/01/2010), envolvendo os períodos seco e chuvoso. As análises foram executadas para vazão, temperatura, pH, condutividade elétrica, cálcio, magnésio, sódio, potássio, sílica, cloreto, sulfato, fosfato e nitrato. Os resultados indicam que os parâmetros cálcio, magnésio e nitrato possuem um comportamento semelhante, ou seja, aumentam de montante (P1 e P3, sedimentos da Formação Itaqueri e a unidade de relevo Colinas Médias) para jusante (P2 e P4, Morrotes Alongados e Espigões associados às rochas ígneas da Formação Serra Geral). No Rio Jaú (P5 e P6) que também drena os basaltos da Formação Serra Geral, com exceção de Ca2+, Mg2+ e Cl- todos os outros parâmetros analisados possuem uma concentração maior no ponto P6, próximo à foz com o Rio Tietê. No entanto, a soma total de cátions e ânions (t/km2 /ano) é maior no ponto P5, devido à alta concentração de Ca2+ e Mg2+ no local. Como as rochas da bacia do Rio Jaú não possuem minerais portadores de Cl- , NO3 - , PO4 3- e SO4 2- como constituintes principais, a denudação química (t/ano) na bacia do Rio Jaú foi calculada com base na concentração de Ca2+, Mg2+, Na+ , K+ e SiO2 (solução lixiviada dos minerais que compõem as rochas da bacia). Os resultados indicaram que a bacia do Rio Jaú exporta cerca de 16.000 toneladas de material alterado por ano ao Rio Tietê.
Geochemical denudation and implications in composition of surface waters from Jaú River Basin (SP)